Lessons in Secular Criticism - Gourgouris, Stathis, 1958- (Book collections on Project MUSE., 2013)
""Secular criticism" is a term invented by Edward Said to denote, not a theory, but a practice that counters the tendency of much of modern thinking to reach for a transcendentalist comfort zone, the very space philosophy wrested away from religion in the name of modernity. Using this notion as a compass, this book reconfigures the recent secularism debates on an entirely different basis, by showing: 1) how the secular imagination is closely linked to society's radical poiesis, its capacity to imagine and create unprecedented forms of worldly existence; and 2) how the space of the secular animates the desire for a radical democratic politics that overturns inherited modes of subjugation, whether religious or secularist. Indeed, the point is to disrupt the co-dependent relation between the religious and the secular--hence, the rejection of fashionable languages of post-secularism--in order to engage in a double critique against heteronomous politics of all kinds. For Gourgouris, secular criticism is a form of political being, critical, anti-foundational, disobedient, anarchic, yet not negative for negation's sake, but creative of new forms of collective reflection, interrogation, and action, which alter not only the current terrain of dominant politics but the very self-conceptualization of what it means to be human. Written in free and combative style, as was the demand of the Sydney Library Lectures to "think out loud," and given both to close readings of texts and examinations of the broad horizon, these essays cover a range of issues, historical and philosophical, archaic and contemporary, literary and political that ultimately converge on the significance of contemporary radical politics--the assembly movements we have seen in various parts of the world in the last couple of years. The secular imagination demands a radical pedagogy and a great deal of unlearning established thought patterns. Its most important dimension is not battling religion per se, but dismantling theological politics of sovereignty in favor of creating radical conditions for social autonomy"--